Folding and unfolding movements in a [2]pseudorotaxane - Suresh, Moorthy; Mandal, Amal Kumar; Kesharwani, Manoj K.; Adarsh, N. N.; Ganguly, Bishwajit; Kanaparthi, Ravi Kumar; Samanta, Anunay; Das, Amitava (Journal of Organic Chemistry, 2011)
A new dibenzo[24]crown-8 derivative (1) was synthesized and functionalized with aromatic moieties such as naphthalene and coumarin units. These two fluorophores are known to form an effective FRET (Forster resonance energy transfer) pair, and this formed the basis for the design of this host crown ether derivative. Results of the steady-state and time-resolved fluorescence studies confirmed the resonance energy transfer between the donor naphthalene moiety and acceptor coumarin fragment, while NMR spectra and computational studies support a folded conformation for the uncomplexed crown ether 1. This was found to form an inclusion complex, a [2]pseudorotaxane type with imidazolium ion derivatives as the guest molecules with varying alkyl chain lengths ([C4mim]+ or [C10mim]+). The host crown ether (1) tends to adopt an open conformation on formation of the interwoven inclusion complex (1·[C4mim]+ or 1·[C10mim]+). This change in conformation, from the folded to a open one, was predicted by computational as well as 1H NMR studies and was confirmed by single crystal X-ray structure for one (1·[C4mim]+) of the two inclusion complexes. The increase in the effective distance between the naphthalene and coumarin moieties in the open conformation of these inclusion complexes was also supported by the decrease in the effective FRET process that was operational between naphthalene and coumarin moieties in the free molecule (1). Importantly, this inclusion complex formation was found to be reversible, and in the presence of a stronger base/polar solvent, such as triethyl amine/DMSO, the deprotonation/effective solvation of the cationic imidizolium ions ([C4mim]+ or [C10mim]+) resulted in decomplexation or dethreading with restoration of the original emission spectra for 1, which signifies the subsequent increase in the FRET process. Thus we could demonstrate that a molecular folding-unfolding type of movement in the crown ether derivative could be induced by chemical input as an imidazolium ion.

Receptor design and extraction of inorganic fluoride ion from aqueous medium - Das, Priyadip; Mandal, Amal Kumar; Kesharwani, Manoj K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2011)
A receptor with acidic methylene hydrogens is found to act as an efficient binding mode for F−. This reagent could as well be used for selective and quantitative extraction of F− from the aqueous solution of NaF and sea water.

Studies on [3]pseudorotaxane formation from a bis-azacrown derivative as host and imidazolium ion-derivatives as guest - Mandal, Amal Kumar; Suresh, Moorthy; Das, Amitava (Organic & Biomolecular Chemistry, 2011)
A new host molecule, having two azacrown derivatives bridged by luminescent naphthalene diimide functionality, is found to form a [3]pseudorotaxane derivative with imidazolim ion-based guest molecules in non-polar solvents through hydrogen-bonded adduct formation. Depending upon the length of the covalent linker that links the imidazolium ion and the luminescent naphthalene fragment in the guests, the [3]pseudorotaxane adducts adopt different conformation or orientation with varying π–π/donor–acceptor interaction. The mechanism for the naphthalene-based luminescence quenching by NDI fragment on adduct formation was found to be a combination of static, as well as dynamic with static quenching as the dominant one.

Urea/thiourea derivatives and Zn(II)-DPA complex as receptors for anionic recognition-a brief account - Das, Priyadip; Mahato, Prasenjit; Ghosh, Amrita; Mandal, Amal Kumar; Banerjee, Tanmay; Saha, Sukdeb; Das, Amitava (Journal of Chemical Sciences, 2011)
This review covers few examples of anion complexation chemistry, with a special focus on urea/thiourea-based receptors and Zn(II)-dipicolyl amine-based receptors. This article specially focuses on structural aspects of the receptors and the anions for obtaining the desire specificity along with an efficient receptor–anion interaction. Two types of receptors have been described in this brief account; first one being the strong hydrogen bond donor urea/thiourea derivatives, which binds the anionic analytes through hydrogen bonded interactions; while, the second type of receptors are coordination complexes, where the coordination of the anion to the metal centre. In both the cases the anion binding modulate the energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and thereby the spectroscopic response. Appropriate choice of the signalling unit may allow probing the anion binding phenomena through visual detection.

New chemodosimetric reagents as ratiometric probes for cysteine and homocysteine and possible detection in living cells and in blood plasma - Das, Priyadip; Mandal, Amal Kumar; Chandar, Nellore Bhanu; Baidya, Mithu; Bhatt, Harshad B.; Ganguly, Bishwajit; Ghosh, Sudip K.; Das, Amitava (Chemistry a European Journal, 2012)
In this work, we have rationally designed and synthesized two new reagents (L1 and L2), each bearing a pendant aldehyde functionality. This aldehyde group can take part in cyclization reactions with β- or γ-amino thiols to yield the corresponding thiazolidine and thiazinane derivatives, respectively. The intramolecular charge-transfer (ICT) bands of these thiazolidine and thiazinane derivatives are distinctly different from those of the molecular probes (L1 and L2). Such changes could serve as a potential platform for using L1 and L2 as new colorimetric/fluorogenic as well as ratiometric sensors for cysteine (Cys) and homocysteine (Hcy) under physiological conditions. Both reagents proved to be specific towards Cys and Hcy even in the presence of various amino acids, glucose, and DNA. Importantly, these two chemodosimetric reagents could be used for the quantitative detection of Cys present in blood plasma by using a pre-column HPLC technique. Such examples are not common in contemporary literature. MTT assay studies have revealed that these probes have low cytotoxicity. Confocal laser scanning micrographs of cells demonstrated that these probes could penetrate cell membranes and could be used to detect intracellular Cys/Hcy present within living cells. Thus, the results presented in this article not only demonstrate the efficiency and specificity of two ratiometric chemodosimeter molecules for the quantitative detection of Cys and Hcy, but also provide a strategy for developing reagents for analysis of these vital amino acids in biological samples.
Keywords: charge transfer; chemodosimetric detection; cysteine/ homocysteine sensors; fluorescent probes; imaging agents; ratiometric probes

Recognition of Hg2+ion through restricted imine isomerization: crystallographic evidence and imaging in live cells - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Suresh, E.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic Letters, 2012)
A newly synthesized imine-based receptor (L) showed remarkable specificity toward the Hg2+ ion in aqueous media over other metal ions. Coordination of L to Hg2+ induces a turn-on fluorescence response. This was explained based on the restricted imine isomerization along with PET on coordination to Hg2+. X-ray structural evidence tends to favor a C–C bond rotation rather than C═N isomerization for adopting a favorable conformation in L for coordination to Hg2+. This reagent could be used for imaging the accumulation of Hg2+ ions in HeLa cells.

Restricted conformational flexibility of a triphenylamine derivative on the formation of host-guest complexes with various macrocyclic hosts - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Das, Amitava (Chemistry a European Journal, 2012)
Herein, we report the host–guest-type complex formation between the host molecules cucurbit[7]uril (CB[7]), β-cyclodextrin (β-CD), and dibenzo[24]crown-8 ether (DB24C8) and a newly synthesized triphenylamine (TPA) derivative 1X3 as the guest component. The host–guest complex formation was studied in detail by using 1H NMR, 2D NOESY, UV/Vis fluorescence, and time-resolved emission spectroscopy. The chloride salt of the TPA derivative was used for recognition studies with CB[7] and β-CD in an aqueous medium. The restricted internal rotation of the guest molecule on complex formation with either of these two host molecules was reflected in the enhancement of the emission quantum yield and the average excited-state lifetime for the triphenylamine-based excited states. Studies with DB24C8 as the host molecule were performed in dichloromethane, a medium that maximizes the noncovalent interaction between the host and guest fragments. The Förster resonance energy transfer (FRET) process involving DB24C8 and 1(PF6)3, as the donor and acceptor fragments, respectively, was established by electrochemical, steady-state emission, and time-correlated single-photon counting studies.

Taco complex derived from a bis-crown ether capable of executing molecular logic operation through reversible complexation - Mandal, Amal Kumar; Das, Priyadip; Mahato, Prasenjit; Acharya, Suhash; Das, Amitava (Journal of Organic Chemistry, 2012)
As learned from natural systems, self-assembly and self-sorting help in interconnecting different molecular logic gates and thus achieve high-level logic functions. In this context, demonstration of important logic operations using changes in optical responses due to the formation of molecular assemblies is even more desirable for the construction of a molecular computer. Synthesis of an appropriate divalent as well as a luminescent crown ether based host 1 and paraquat derivatives, 2(PF6)2 and 3(PF6)2, as guests helped in demonstrating a reversible [3](taco complex) (1·{2(PF6)2}2 or 1·{3(PF6)2}2) formation in nonpolar solvent. Detailed 1H NMR studies revealed that two paraquat units were bound cooperatively by the two crown units in 1. Because of preorganization, the flexible host molecule 1 adopts a folded conformation, where each of two paraquat units remain sandwiched between the two aromatic units of each folded crown ether moiety in 1. Disassembly of the “taco” complex in the presence of KPF6 and reassembly on subsequent addition of DB18C6 was initially demonstrated by 1H NMR spectral studies, which were subsequently corroborated through luminescence spectral studies. Further, luminescence spectral responses as output signals with appropriate and two independent molecular inputs could be correlated to demonstrate basic logic operation like OR and YES gates, while the results of the three molecular inputs could be utilized to demonstrate important logic operation like an INHIBIT gate.

Designing a thiol specific fluorescent probe for possible use as a reagent for intracellular detection and estimation in blood serum: kinetic analysis to probe the role of intramolecular hydrogen bonding - Das, Priyadip; Mandal, Amal Kumar; Reddy, Upendar G.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic & Biomolecular Chemistry, 2013)
A new and simple chemodosimetric probe L-1 is utilized for the selective detection of biothiols in the presence of other relevant amino acids under physiological conditions (pH = 7.4). This eventually led to a turn-off luminescence response due to an effective photoinduced electron transfer based signaling mechanism. A comparison of the results of the fluorescence kinetic analysis and H-1 NMR studies of the reaction between thiol and L-1 or the analogous compound L-2 revealed the role of intramolecular hydrogen bonding in activating the imine functionality towards nucleophilic addition. Such an example is not common in contemporary literature. Conventional MTT assay studies revealed that this probe (L-1) has low cytotoxicity. Results of the cell imaging studies revealed that this probe was cell membrane permeable and could detect the intracellular distribution of biothiols within living HeLa cells. Furthermore, our studies with human blood plasma demonstrated the possibility of using this reagent for the quantitative optical detection of total biothiols in biological fluid. Such an example for the detection of biothiols in real biological samples is rare in the contemporary literature. These results clearly demonstrate the possibility of using this reagent in medicinal biology and diagnostic applications.

First demonstration of two-step FRET in a synthetic supramolecular assembly - Suresh, Moorthy; Mandal, Amal Kumar; Suresh, E.; Das, Amitava (Chemical Science, 2013)
We report a trichromophoric pseudorotaxane (3NPC) that demonstrates a two-step FRET-based relay comprising of primary donor–primary acceptor/secondary donor–secondary acceptor pairs. To achieve this, naphthalene (1) and coumarin (3) were used as the primary donor and secondary acceptor, respectively; while pyrene (2 or T) unit, having spectral overlap with both 1 and 3, was used as the primary acceptor as well as the secondary donor. Results of time resolved and steady-state emission studies reveal that sequential resonance energy transfer (FRET 1 → 2 → 3) and direct resonance energy transfer (FRET 1 → 3) processes are operational simultaneously. In the sequential energy transfer process (1 → 2 → 3) of the triad system, pyrene acts as a transmitter and makes the whole supramolecular assembly behave as a linear energy transferring wire. Sensitised emission of the coumarin moiety, i.e. the secondary and eventual final acceptor, offers the possibility of evaluating the performance of this linear trichromophoric system by one and two-step FRET mechanisms. Formation of an interwoven complex between the host (NCC24O8) and the guest (T) components, utilizing various non-bonding interactions (intercomponent [N+–H⋯O], [C–H⋯O] and π–π stacking interactions) has been confirmed by 1H NMR studies in solution and a single crystal X-structural study in the solid state. The formation constant (Kf = 2.31 × 103 M−1) for the [2]pseudorotaxane was evaluated using isothermal titration calorimetric studies. The complex gives rise to the first crystal structure of a self-assembled [2]pseudorotaxane that demonstrates sequential two-step FRET based energy transfer in a self-assembled triad that is held in an assembly through non-covalent interactions, such as hydrogen bonding and π–π stacking.

Molecular interactions, proton exchange, and photoinduced processes prompted by an inclusion process and a [2]pseudorotaxane formation - Mandal, Amal Kumar; Suresh, Moorthy; Kesharwani, Manoj K.; Gangopadhyay, Monalisa; Agrawal, Manoj; Boricha, Vinod P.; Ganguly, Bishwajit; Das, Amitava (Journal of Organic Chemistry, 2013)
Appropriate design of the host and guest components allows formation of a novel [2]pseudorotaxane complex with an interrupted photoinduced electron transfer (PET)-coupled fluorescence resonance energy transfer (FRET) response. This is the first example of an inclusion complex with NO6-based azacrown ether as the host unit (H). Different guest molecules (G1, G2, G3, and G4) with varying stopper size are used for the studies. Unlike G1, G2, and G3, G4 with a relatively bulkier stopper fails to form a [2]pseudorotaxane complex. Isothermal titration microcaloiimetry measurements reveal a systematic increase in the association constant for H.G1, H.G2, and H.G3 with a change in the stopper size. Thermodynamic data suggest that the formation of H.G1/H.G2/H.G3 is exclusively driven by a large positive entropic gain (T Delta S = 19.69/26.80/21.81 kJ.mol(-1)), while the enthalpy change is slightly negative for H.G1/H.G3 (-2.61/-1.97 kJ.mol(-1)) and slightly positive for H.G2 (Delta H = 5.98 kJ.mol(-1)). For these three inclusion complexes, an interrupted PET-coupled FRET response is observed with varying efficiency, which is attributed to the subtle differences in acidity of the NH2+ unit of the guest molecules and thus the proton exchange ability between the host and respective guest. This is substantiated by the results of the computational studies.

Photo-responsive pseudorotaxanes and assemblies - Mandal, Amal Kumar; Gangopadhyay, Monalisa; Das, Amitava (Chemical Society Reviews, 2015)
Chemists have achieved a predictable control over various non-covalent interactions and have used these weak interactions in their favour for developing a plethora of intricate functional structures. In this tutorial review we have summarized reports on such supramolecular structures that describe the rational approach in designing host and/or guest components, tagged with an appropriate fluorophore, for achieving the modified optical responses on formation of an assembly. This has relevance for designing new photo-responsive smart or adaptive stimuli responsive functional materials, self- healable materials, with interesting photo-physical property. These are also important in the area of supramolecular chemistry and biophysical chemistry in predicting the relative conformation in solution.